Primary PCI as the preferred reperfusion therapy in STEMI: it is a matter of time. Issue 5 (13th February 2009) - Terkelsen, C J; Christiansen, E H; Sørensen, J T; Kristensen, S D; Lassen, J F; Thuesen, L; Andersen, H R; Vach, W; Nielsen, T T
Abstract : There is a continuing controversy about the acceptable time-window for primary percutaneous coronary intervention (PPCI) in patients with ST-elevation myocardial infarction (STEMI). Recent American and European guidelines recommend PPCI if the delay in performing PPCI instead of administering fibrinolysis (PCI-related delay) is <60 min and the presentation delay is more than 3 h. Based on a review of the literature, this viewpoint recommends a revision of the guidelines. The evidence supports an acceptable PCI-related delay of 80–120 min and PPCI as the better reperfusion strategy also in the early incomers. Furthermore, the previous assumption that PPCI is less time-dependent than fibrinolysis is questioned. To maximise the number of patients with STEMI eligible for PPCI the optimal logistic may be to establish the diagnosis in the prehospital phase, to bypass local hospitals and re-route patients directly to catheterisation laboratories running 24/7.